Developing an Indigenous, Entry-Level Master ' s Degree Program in a Country with an Emerging OT Profession - Lesley A. Garcia; Julie D. Kugel; Heather Javaherian-Dysinger; Heather Javaherian-Dysinger; Esther Huecker (Scholarworks @ WMU, 2016)
In the Republic of Trinidad and Tobago the full range of physical, mental, psychological, and socially derived problems of occupational engagement exist. Occupational therapy is often a part of the health care team to address these challenges; however, the profession is at an emergent stage in the country. This paper describes a process used for the development of an indigenous entry-level master's degree program in occupational therapy. The process was also supported and enhanced by the collaborative relationships among key stakeholders, including global partners. A qualitative design process was used to analyze the health care needs, barriers, and strategies that impact the sustainability of the proposed program. This included 47 survey respondents, 10 semi-structured interviews, and a focus group. The findings led to the development of curricular threads that informed the curricular framework of the program. The curricular framework will safeguard the sustainability of the program and the clinical relevance of its content and methods relative to the community the graduates will serve. Systematic review of curricular design and program outcomes is needed to enhance the intended learning experience of the occupational therapy students.